Study of the evaluation system for the specialized sports quality of junior male volleyball players - Liang, R. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume III: Statistics and Managment in Sports., 2008)
This paper plans to define the primary indexes for the specialized sports quality of junior male volleyball players. It constructs the structural system, the evaluation model and evaluation criteria for the specialized sports quality of junior male volleyball players. It hopes that this study could help the coaches to check the training effect thoroughly and effectively, and it could serve as the reference system for the adjusting of training schedule and the controlling of sport training process to realize the target of scientific training.